Study On Reduction of Exposure Dose through Development of Field Display Devices of Radiation Fluoroscopy - Kim, Gha-Jung; Koo, Bon-Yeoul (International Journal of Engineering and Technology, 2018)
Background: This study was to develop a field-of-view display system for radiographic imaging equipment for the purpose of reducing the exposure dose when using the C-arm fluoroscopy device.Methods: To evaluate its effectiveness, the time was measured and the doses injected into the instrument during the time of exposure to radiation were compared.Findings: As a result, when the developed field device was installed, the radiation exposure time for finding the target organ was 23.90±3.30 sec before installation, 8.22±1.90 sec after installation, and 66% of radiation exposure time was decreased. It was found that the dose was reduced by 62% from 16.57±1.28 mGy to 6.27±1.36 mGy after installation.Improvement: It was confirmed that the irradiation field display device of the fluoroscopic device developed through this study can reduce the radiation exposure time by visually displaying the radiation exposure area, thereby effectively reducing the exposure dose.